INCONGRUENCIA EN EL PRINCIPIO DE PROPORCIONALIDAD PARA TIPIFICAR Y SANCIONAR LOS DELITOS DERIVADOS DE LOS ILÍCITOS EN LA IMPORTACIÓN O EXPORTACIÓN DE MERCANCÍAS - Arévalo Quizhpe., Walter Xavier (2016)
This research work, we have developed in the legal field of public law, specifically on the shortcomings that exist in the Criminal Code of Integral, concerning the criminalization and punishment of crimes arising from the customs tax liability. In customs offenses there misappropriation of tax liability, the evasion occurring as a result it becomes customs offense and punishable under the Criminal Code of Integral. The commission of these crimes affecting the national treasury, especially when to criminalize and punish crimes of custom the principle of proportionality provided for in the Constitution, by stating very mild penalties against damage caused is contrary. Therefore, there is inconsistency in the constitutional principle of proportionality to criminalize and punish crimes resulting from the illegal importation or exportation of goods; consequently, it causes economic damage to this country when the evasion of tax liability occurs. So, it is necessary to establish penalties and sanctions more rigorously for the intended customs offenses in the Code of Integral Penal since been regulated penalties and greatly reduced sanctions against such behavior, which contravenes the principle of proportionality set out in the Constitution. 5 When referring to the sanctions and penalties provided for customs offenses, let us say that we consider inadequate, since the commission of illegal social harms, financially and economically the country; for that reason, they should worsen the penalties for these crimes in order to achieve a better realization of justice and stop crimes of smuggling and customs fraud. Our Constitution and principle of immediate application, states as one the primary goals of the State, the realization of justice in harmony with the good life of all Ecuadorians; as such, it should better clarify the purpose of the Act, in order to effectively achieve its purposes sense. As such, this research aims to implement the principle of proportionality, prescribed in the Constitution regarding the definition and punishment of customs offenses under the Criminal Code of Integral; since there is kindness in the establishment of such sanctions.